Penggunaan Pupuk Organik Asal Ternak Sapi pada Kelapa Sawit Umur ≥ 20 Tahun - Zulia Jati, Putri; Yuhendra; Dimas Setiawan, Bagus (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2023)
Fertilization of oil palm plantations >20 years old, tends to be reduced especially inorganic fertilizers. It is important to use the optimum fertilizer, particularly organic fertilizer, in order for their yield to remain stable. Cattle manure provides yields the raw ingredient for organic fertilizer. The objective of this research is to determine the impact of both solid and liquid compost on the productivity of oil palm trees older than 20 years. With treatment A being 5 kg of solid compost, treatment B being 3 kg of solid compost, treatment C being 5 liters of liquid compost, treatment D being 2.5 liters of liquid compost, treatment E being 3 kg of solid compost, and 2.5 liters of liquid compost, and treatment F being no composting, the study employed a completely randomized design. FFB production, bunch number, bunch weight, the longest time between harvests, and frequency of harvesting were measured for a year. There are five replications of each treatment. Descriptive statistics and analysis of variance were used to analyze the data. Observations showed that there was no significant difference between treatments in observing. The results of this research indicate that using cattle manure as fertilizer for oil palm plantations better yields than palm oil plantations without the use of organic fertilizer. The application of solid fertilizer nonetheless resulted in a production that was approximately equivalent to oil palm production that did not apply compost, whereas fertilizing with 2.5 liters of liquid compost resulted in the highest yield of 192.6 kg/tree/year. Production, trek period, number of bunches, bunch weight, and harvest frequency did not significantly differ between the treatment.